Important Plants for Honey Production in Four Agro Ecological Zones of Uganda - Otim, Agnes S.; Kajobe, Robert; Abila, Patrick P’Odyek; Kasangaki, Patrice; Echodu, Richard (Bee World, 2019)
The diet of honey bees consists of protein-rich pollen and sugar-rich nectar collected separately or synchronously from flowers by foraging worker bees (Kajobe, 2006, 2007). These resources are collected in quantities that exceed colony demands and are stored for dearth periods. The nectar is converted into honey and pollen stored as bee bread (Anderson et al., 2014; Nicolson, 2011). While collecting nectar and pollen, bees deposit pollen from anthers to the stigma resulting in pollination and increased fruit set (Vidal, Jong, Wien, & Morse, 2010). In the USA, Morse and Calderone (2000) estimated the value of crop production achieved through pollination by honey bees alone at $14.6 billion. The value of honey production by bees in Africa is 169,306 tons (faostat.org 2013). Some plants have been observed to be heavily visited by the honey bees while others are less frequently visited (Bendifallah, Louadi, & Doumandji, 2013; Couvillon et al., 2015). Nectar and pollen resource depletion induced by prolonged wet seasons or overheating in the dry seasons is known to cause migration or absconding in African honey bees (Hepburn, 2006; Winston, Otis, & Taylor, 1978).
Keywords: Plants; Honey Production; Agro Ecological Zones; Uganda